Sa1130 the effect of phoenixin-14 on sepsis-induced hepatic injury and impaired intestinal contractility - UPRAK, TEVFİK KIVILCIM (My University, 2020)
Proof systems for the Relativized Propositional Calculus are defined and compared.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)